Financial Structure and Cost of Capital in the Multinational Corporation - Shapiro, Alan C. (Journal of Financial and Quantitative Analysis, 1978)
As the multinational corporation (MNC) becomes the norm rather than the exception, the need to internationalize the tools of domestic financial analysis is apparent. A key question is: What cost-of-capital figure should be used in appraising the profitability of foreign investments? This paper seeks to provide a comprehensive approach to analyze the cost-of-capital question. It begins by extending the weighted cost-of-capital concept to the multinational firm. It then builds on previous research to address the following related topics: national or multinational financial structure norms; the role of parent company guarantees; the costing of various fund sources particularly when exchange risk is present; the impact of tax and regulatory factors; risk and diversification; and joint ventures.